Does This Road Go on Forever? Modelling Sustainability of Infrastructure in Developing Countries. (December 2017) - Streatfeild, Jeremy
There are not enough roads in developing countries but it is not for a lack of spending to address this shortfall. Multilateral and bilateral development agencies have invested billions of dollars to build up new transportation networks because the shortage of road supply constrains trade and economic growth. However, these new roads often do not last as long as initially anticipated so many of the same donors worry that governments will not provide sufficient maintenance of these investments. In turn, economists suggest that weak maintenance performance may be due to low institutional capacity in the recipient country or even a lack of budgetary funds—both easy fixes that warrant an optimal benefit stream according to their economic rate of return in HDM4 models ("ERR"). However, these maintenance reforms have had mixed results which we argue is the result of a deeply entrenched institutional concern that requires intricate analysis and project-tailored reform approaches to remedy. Even then, these reforms may not exhibit incremental benefits for an ERR. In sum, ERR models of roads should include a rigorous political economy analysis as a due diligence prerequisite in order to substantiate any included assumptions of maintenance reforms resulting from a donor project.